Preliminary Pharmacokinetic Study of Repeated Doses of Rifampin and Rifapentine in Guinea Pigs - Dutta, Noton K. (American Society for Microbiology, 2013)
Substitution of rifapentine (RFP) for rifampin (RIF) in the standard antituberculous regimen reduces the time required to cure chronic tuberculosis (TB) infection in mice, but not in guinea pigs. In order to gain insight into these discrepant findings, we conducted a steady-state pharmacokinetic (PK) study in healthy guinea pigs to study the metabolism and autoinduction of RIF and RFP. Both RFP and RIF 25-desacetyl metabolites (desRFP and desRIF, respectively), were detected at low concentrations in the serum of guinea pigs. The metabolite concentrations in guinea pigs are much lower than those seen in humans at steady state.